Constructing a winning programme for an Olympic cycle - Furniss, B. (FINA Golden Coaches Clinic 2016, 2016)
Bill Furniss, Head Coach, British Swimming, talks about "Constructing a Winning Programme for an Olympic Cycle" at the FINA Golden Coaches Clinic 2016 December 4-5th (1:28:20 h).